Cancer Risk and Use of Protease Inhibitor or Nonnucleoside Reverse Transcriptase Inhibitor–Based Combination Antiretroviral Therapy: The D. (15th April 2015) - Bruyand, Mathias; Ryom, Lene; Shepherd, Leah; Fatkenheuer, Gerd; Grulich, Andrew; Reiss, Peter; de Wit, Stéphane; d´Arminio Monforte, Antonella; Furrer, Hansjakob; Pradier, Christian; Lundgren, Jens; Sabin, Caroline
Abstract : Background: The association between combination antiretroviral therapy (cART) and cancer risk, especially regimens containing protease inhibitors (PIs) or nonnucleoside reverse transcriptase inhibitors (NNRTIs), is unclear. Methods: Participants were followed from the latest of D:A:D study entry or January 1, 2004, until the earliest of a first cancer diagnosis, February 1, 2012, death, or 6 months after the last visit. Multivariable Poisson regression models assessed associations between cumulative (per year) use of either any cART or PI/NNRTI, and the incidence of any cancer, non–AIDS-defining cancers (NADC), AIDS-defining cancers (ADC), and the most frequently occurring ADC (Kaposi sarcoma, non-Hodgkin lymphoma) and NADC (lung, invasive anal, head/neck cancers, and Hodgkin lymphoma). Results: A total of 41, 762 persons contributed 241, 556 person-years (PY). A total of 1832 cancers were diagnosed [incidence rate: 0.76/100 PY (95% confidence interval: 0.72 to 0.79)], 718 ADC [0.30/100 PY (0.28–0.32)], and 1114 NADC [0.46/100 PY (0.43–0.49)]. Longer exposure to cART was associated with a lower ADC risk [adjusted rate ratio: 0.88/year (0.85–0.92)] but a higher NADC risk [1.02/year (1.00–1.03)]. Both PI and NNRTI use were associated with a lower ADC risk [PI: 0.96/year (0.92–1.00); NNRTI: 0.86/year (0.81–0.91)]. PI use was associated with a higher NADC risk [1.03/year (1.01–1.05)]. Although this was largely driven by an association with anal cancer [1.08/year (1.04–1.13)], the association remained after excluding anal cancers from the end point [1.02/year (1.01–1.04)]. No association was seen between NNRTI use and NADC [1.00/year (0.98–1.02)]. Conclusions: Cumulative use of PIs may be associated with a higher risk of anal cancer and possibly other NADC. Further investigation of biological mechanisms is warranted.